Drivers and characteristics of wastewater agriculture in developing countries: results from a global assessment - Raschid-Sally, Liqa; Jayakody, Priyantha (International Water Management Institute, 2008)
In 4 out of 5 cities in developing countries, wastewater is used to cultivate perishable crops for urban markets. Such practices create a health risk but provide important livelihood benefits. This study through an analysis of 53 cities in developing countries, contributes to understanding the factors that drive wastewater use. The main drivers are (1) increasing urban water demand without wastewater treatment causing pollution of irrigation water sources; (2) urban food demand favoring agriculture close to cities where water sources are polluted; and (3) lack of cheaper, similarly reliable or safer water sources. Poverty, which constrains the infrastructure needs of urbanization, is an added factor. The study makes policy recommendations stressing on, effectively applying the WHO guidelines, linking investments in water supply with sanitation for maximum beneficial impact on water pollution, and involving actors at both the national and local level, for water quality improvements and health risk reduction.